Short Communication: Morphological diversity and the addition of golden snail protein: Its effect on flavonoid content on Echinacea purpurea - Wina Chandra Ferdyana; Yuli Widiyastuti; Bambang Pujiasmanto; Amalia Tetrani Sakya; ahmad yunus (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ferdyana WC, Widiyastuti Y, Pujiasmanto B, Sakya AT, Yunus A. 2021. Short Communication: Morphological diversity and the addition of golden snail protein: Its effect on flavonoid content on Echinacea purpurea. Biodiversitas 23: 62-66. Echinacea purpurea is a subtropical medicinal plant that contains flavonoids. Flavonoids function as antioxidants and immunomodulators. However, information on the method to increase flavonoid content in E. purpurea is still limited. The golden snail protein increases flavonoid content. The purpose of this study was to determine the best accession and optimal concentration of golden snail protein on biomass production and flavonoid content in E. purpurea. The study used a Factorial Completely Randomized Design (CRD). The first factor was three accessions of E. purpurea (A1, A2, A3); the second factor was 5 levels of the addition of golden snail protein (0 mL/L/week, 10 mL/L/week, 20 mL/L/week, 30 mL/L/week, and 40 mL /L/week). There were differences in morphological characters of three E. purpurea accessions, i.e., stem and the shape of the flower crown. Accession 2 had the highest flavonoid content except for the 10 mL/L/week treatment. The highest increase in flavonoid content in three accessions was obtained in the treatment of 10 mL/L/week gold snail protein by 19% flavonoid content compared to control treatment (0 mL/L/week). The concentration of 0 mL/l/week or control had the lowest flavonoid content.